Injury prevalence in Dutch handball over the season 2018-2019 - Barendrecht, M.; Arnts, T.; van Maanen-Coppens, L. (British Journal of Sports Medicine, 2021)
Background Dutch handball has gained popularity since recent international successes. Downside is the risk of injuries. Objective To gather information on the prevalence and distribution of injuries in Dutch handball for the development and implementation of targeted preventive measures. Design Repeated cross-sectional design. Setting Adolescent and adult handball players active in Dutch leagues of any playing level were invited through social media, club mailings and the website of the Dutch Handball Federation to participate in a monthly online survey. Participants Handball players (16 years or older) were included. In total 1136 respondents (80% female) filled in 4171 monthly questionnaires from September 2018 to June 2019. Risk Factors Outcomes were categorized by sex and playing position. Main Outcome Measurements New injuries (injury incidence) and number of injured players divided by the total number of respondents (prevalence) per body location. Injury definition: 'the inability to fully participate in handball training and/or matches over the last month due to a problem sustained during handball. The Oslo Sports Trauma Research Centre Questionnaire (OSTRCQ) was used to quantify injury severity. Results Of 657 new injuries, the knee (21%), ankle (17%) and shoulder (10%) contributed similarly in both sexes and the lower leg predominantly in female players (10%). Overall injury prevalence was 43% (female 46%, male 34%). Most prevalent body locations and their mean (standard deviation (sd)) OSTRCQ-scores were the knee (8.8%; OSTRCQ 61, sd 26), shoulder (4.4%; OSTRCQ 50, sd 22), ankle (4.0%; OSTRCQ 55, sd 27) and the lower leg (3.1%; OSTRCQ 56, sd 26). For all playing positions the knee showed the highest prevalence followed by the shoulder (wings and backs) and/or ankle (backs, pivots and goalies). Conclusions The high prevalence of knee, ankle and shoulder injuries in both sexes in Dutch handball emphasizes the need for implementation of preventive measures. Preventive training programs already proven successful in handball populations from other countries can be implemented in Dutch handball as well.